Learning Transformation in the Digital Age: The Role of Islamic Education Teachers in Implementing Constructivism Learning - suwendi, suwendi; Anitra Firdaus, Salsabila (LPPM Universitas Ibn Khaldun, Bogor, 2025)
The development of digital technology has significantly changed the educational landscape, including in Islamic Religious Education (PAI) learning. This study aims to identify the role of PAI teachers in implementing constructivist learning in the digital era, as well as the challenges and opportunities faced. This research uses a qualitative approach with a literature review design focusing on literature reviews from various reading media. The results showed that PAI teachers are important in facilitating students' active, critical, and creative learning through different digital platforms. However, teachers also face challenges such as limited infrastructure, lack of training, and resistance from some students. This study concludes that efforts are needed to improve teachers' digital competencies, develop relevant curricula, and provide adequate infrastructure to support the implementation of constructivist learning in the digital era.